062PS The Role of Rapid Systematic Reviews for Development of Rapid Guidance in Health Care and Health Policy Settings. (15th August 2013) - Koster, M; Garritty, C; Gallagher, C; Schunemann, H; Norris, S
Abstract : Background: Conducting systematic evidence reviews on a set of focused clinical questions has become one of the "gold standards" for development of "trustworthy" clinical guidance. Time, resource constraints, and other issues, however, may require the application of more pragmatic means for reviewing the evidence to support rapid guidance development. Target Group, Suggested Audience: Developers of guidance for health systems and health policy settings. Objectives/Goals: To actively engage panellists and session participants in a discussion of the role of rapid systematic reviews in the development of rapid guidance, the strengths and limitations of rapid vs. full/complete systematic review methods, and lessons learned from recent national and international rapid review and guidance efforts within health care and health policy settings. Description of Session and Speaker Topics: Chantelle Garritty will discuss OHRI's rapid review work with the Ottawa Hospital Technology Assessment Programme, and the Cochrane Collaboration's new "Cochrane Response" rapid review methodology; Catherine Gallagher will present results of a pilot Cochrane Response rapid review within the GMU Health System, and organisation of an international group to develop rapid review standards; Holger Schunemann will present examples of rapid systematic reviews and their value in rapid guidance development; and Susan Norris will present on the WHO's development of rapid guidance in the setting of urgent public health needs. Marguerite Koster will moderate the discussion.